Syntheses, Structures and Biological Activity of Some Schiff Base Metal Complexes (Baghdad Science Journal, 2022)
Four new binuclear Schiff base metal complexes [(MCl2)2L] {M = Fe 1, Co 2, Cu 3, Sn 4, L = N,N’-1,4-Phenylenebis (methanylylidene) bis (ethane-1,2-diamine)} have been synthesized using direct reaction between proligand (L) and the corresponding metal chloride (FeCl2, CoCl2, CuCl2 and SnCl2). The structures of the complexes have been conclusively determined by a set of spectroscopic techniques (FT-IR, 1H-NMR, and mass spectra). Finally, the biological properties of the complexes have been investigated with a comparative approach against different species of bacteria (E. coli G-, Pseudomonas G-, Bacillus G+, Staphylococcus G+, and Streptococcus G+).